Contested spaces and everyday peace politics in Northern Ireland - Brennan, Sean (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
In 2022, the United Kingdom downgraded the security threat in Northern Ireland from “severe” to “substantial”, first set in 2010. The latter means that an attack is likely but not highly likely. For many analysts and political observers, the twenty-five years of peace that followed the signing of the Belfast/Good Friday Agreement (B/GFA) though interspersed with periods of political stalemate, have led to an overall external sense the conflict has ended. This downgrading of the security threat in Northern Ireland appears to confirm this sense of a settled peace. Still, the type of peace that has been achieved, and particularly the political dynamics regarding contentious spatial issues, continue to shape the quality of peace experienced by the local population. In turn, it is precisely this everyday quality of peace that reflects the real success, or failure, of various peacebuilding efforts as such practices produce the empirical evidence of sustainable reconciliation or continue sectarian divisions in a post-conflict space.
Keywords: Severna Irska; sporna področja; Velikonočni sporazum; vsakodnevne mirovne politike in prakse; vzpostavitev miru